Respon Media Atas Polemik Tes PCR (Tinjauan atas Konten Majalah Tempo dan Media Online Tempo.co) - Nurdin Sibaweh (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
This research is aimed to explain how Tempo magazine edition 1 November 2021 and Tempo.Co on 1-7 November 2021 coverage responded to the PCR test policy, considering that the policy has caused polemics and has become a discourse that grabbed the public attention. This study used a qualitative approach to content analysis which was carried out on Tempo Magazine and Tempo.Co on 1-7 November 2021. Before conducting content analysis, the researcher first grouped the news carried out by Tempo Magazine and Tempo.co on that date. The results show that the content of Tempo magazine 1 November 2021 edition presented opinions and news from the investigation that the PCR test business was controlled by government officials, politicians and big businessmen who were suspected of taking advantage in the midst of the Covid-19 pandemic, and business interest was indicated in the requirements for taking PCR test before flight. Meanwhile Tempo.co, from 1-7 November 2021, presented news content that was quite intensive and also critical of the PCR test policy, emphasizing the involvement of two ministers involved in the PCR business, namely Luhut Binsar Panjaitan as the Coordinating of Minister for Maritime Affairs and Investment of the Republic of Indonesia and Erick Thohir as the Minister of State-owned Enterprises (BUMN).